2014
DOI: 10.1002/embr.201337631
|View full text |Cite
|
Sign up to set email alerts
|

PICK 1 links Argonaute 2 to endosomes in neuronal dendrites and regulates mi RNA activity

Abstract: MicroRNAs fine-tune gene expression by inhibiting the translation of mRNA targets. Argonaute (Ago) proteins are critical mediators of microRNA-induced post-transcriptional silencing and have been shown to associate with endosomal compartments, but the molecular mechanisms that underlie this process are unclear, especially in neurons. Here, we report a novel interaction between Ago2 and the BAR-domain protein, PICK1. We show that PICK1 promotes Ago2 localization at endosomal compartments in neuronal dendrites a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 31 publications
4
49
0
Order By: Relevance
“…We analysed two dendritically regulated UTRs; LIMK1 , which is regulated by miR‐134 (Schratt et al , 2006), and APT1 , which is regulated by miR‐138 (Siegel et al , 2009). Both of these miRNAs have been shown previously to regulate dendritic spine morphology (Schratt et al , 2006; Siegel et al , 2009), and we previously demonstrated that NMDAR activation increased translational repression of the LIMK1 reporter via miR‐134 and of the APT1 reporter via miR‐138 within 10 min after stimulation (Antoniou et al , 2014; Rajgor et al , 2017). Knockdown of Ago2 by shRNA caused a dramatic increase in expression of both reporter constructs, consistent with a deficit of miRNA‐mediated translational repression, and NMDAR stimulation had no effect under these conditions (Fig 5A and B).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…We analysed two dendritically regulated UTRs; LIMK1 , which is regulated by miR‐134 (Schratt et al , 2006), and APT1 , which is regulated by miR‐138 (Siegel et al , 2009). Both of these miRNAs have been shown previously to regulate dendritic spine morphology (Schratt et al , 2006; Siegel et al , 2009), and we previously demonstrated that NMDAR activation increased translational repression of the LIMK1 reporter via miR‐134 and of the APT1 reporter via miR‐138 within 10 min after stimulation (Antoniou et al , 2014; Rajgor et al , 2017). Knockdown of Ago2 by shRNA caused a dramatic increase in expression of both reporter constructs, consistent with a deficit of miRNA‐mediated translational repression, and NMDAR stimulation had no effect under these conditions (Fig 5A and B).…”
Section: Resultsmentioning
confidence: 70%
“…While the interaction between Ago2 and MOV10 was unaffected by S387 mutations, association with DDX6 showed a similar pattern as GW182 binding (Fig 3A). We previously described an interaction between Ago2 and the BAR domain protein PICK1, which dissociates in response to NMDAR stimulation (Antoniou et al , 2014; Rajgor et al , 2017). This interaction was unaffected by S387 mutations in Ago2 (Fig 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the ER, cellular endosomes might be involved in the process of RNA silencing: AGO2 has been found in both recycling endosomes (Antoniou et al, 2014) and multivesicular bodies (MVB) (Gibbings et al, 2009). MVBs are formed by the invaginations of endosomes and subsequent formation of so-called intraluminal vesicles (ILV) (reviewed in (Kowal et al, 2014)).…”
Section: The Localization Of Rna-silencing Machinery In the Cellmentioning
confidence: 99%
“…In flies and humans, AGO subfamily proteins are reported to localize at non-membranous bodies such as P-bodies and/or membranous organelles such as endoplasmic reticulum (ER), multivesicular bodies (MVBs) and Golgi [161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179][180].…”
mentioning
confidence: 99%